Comparison of Islamic Economic Institutions in United Arab Emirates and Russia for Indonesia’s Sustainable Development - Pamungkas Putra, Bayu Euro; Naufal Luthfi Alifa (Jurnal Internasional Ekonomi Islam, 2025)
Introduction: Islamic economics emerges as an alternative system emphasizing justice, ethics, and sustainability amid global economic challenges. The United Arab Emirates and Russia represent two contrasting contexts, with the United Arab Emirates as a Muslim-majority nation and Russia as a non-Muslim state, yet both demonstrate significant institutional development of Islamic economics. Objective: This study aims to compare the institutional dynamics of Islamic economic systems in the United Arab Emirates and Russia and analyze their implications for strengthening sustainable Islamic economic development in Indonesia. Method: The study uses a qualitative method with a comparative case study approach. Data were obtained from government policies, official financial reports, and reputable academic journals discussing Islamic finance development in both countries. Analysis was conducted descriptively and comparatively through data reduction, presentation, and conclusion drawing. Result: The United Arab Emirates has successfully institutionalized Islamic finance through strong regulatory frameworks, integrated governance, and technological innovation, positioning Dubai as a global hub for Islamic finance. Meanwhile, Russia has adopted an adaptive and educational approach by developing Islamic finance in regions such as Tatarstan within a hybrid legal system and through international collaboration, despite operating under a secular framework. Implication: The study concludes that Indonesia can integrate the United Arab Emirates’s regulatory strength and Russia’s social inclusivity to build an ethical, inclusive, and sustainable Islamic economic institution aligned with maqasid al-shariah and the Sustainable Development Goals (SDGs).